Peranan Hukum Keluarga Islam Di Indonesia Dalam Mencegah Kekerasan Dalam Rumah Tangga (KDRT) - Asrianto, Lalu; Hamim, Khairul; Wathoni, Lalu Muhammad Nurul (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2025)
10-60% of married women in various parts of the world have experienced domestic violence, including Indonesia, which is a taboo for society and the government. Therefore, this study will explain the role of family law in dealing with KDRT. The research method used is Qualitative with a Library Study approach by collecting data from various sources, such as laws, journals, articles, and books. Data is analyzed by identifying existing patterns and trends, and presenting findings that are relevant to the topic discussed. The results of this study explain that the role of Islamic family law in preventing domestic violence can be in the form of clarity of the rights and obligations of husband and wife, the age limit for marriage and the existence of a marriage agreement to emphasize the rules that apply in a marriage.